New treatment for cocoa disease - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
A new chemical and injection technique using spring-loaded syringes has been developed in Papua New Guinea to fight blackpod disease and canker in cocoa. Neutralized phosphoric acid fungicide is injected directly into the trunk of infected trees....